GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 1328673 species occurrences available in GBIF matching the query: Country: Poland HasGeospatialIssue: false HasCoordinate: true. The dataset includes 1328673 records from 318 constituent datasets: 1 records from The Diptera Site. 27 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1236 records from Insect Collection (CeStuBio). 5709 records from Coleoptera of Piska Forest. 113 records from University of Vienna, Institute for Botany - Herbarium WU. 2546 records from The atlas of butterflies in Kraków. 42 records from MVZ Mammal Collection (Arctos). 3204 records from Faunal Inventory of Morysin Nature Reserve. 288 records from Fungi of Słowiński National Park, Poland. 547 records from LACM Entomology Collection. 31 records from Tromsø Museum, Bryophytes. 74 records from Orthopteroidea. 511 records from Coleoptera of Swierklaniec Forest. 6660 records from Weevils of the Tatra Mts.. 30 records from Bee Biology and Systematics Laboratory. 97 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 54 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 17 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 77 records from AntWeb. 5733 records from Small Mammal Research Database. 53 records from Naturalis Biodiversity Center (NL) - Botany. 39 records from Herbarium Senckenbergianum (GLM) - Lichenes. 3 records from Plecoptera. 50 records from Fishbase. 20 records from Occurrence records of southern African aquatic biodiversity. 33 records from NPL collections. 627 records from University of Alberta Vascular Plant Herbarium (ALTA). 338 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 123 records from The avian collection at the Natural History Museum, Oslo, Norway. 400 records from Lyman Entomological Museum (LEMQ). 8542 records from Collection of Coleoptera. 17 records from published_chenopodium_vulvaria_observations. 1 records from BioFokus. 3 records from Culture Collection of Cryophilic Algae. 1 records from University of Florida Vertebrate Paleontology. 1 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 9088 records from Flora of Słowiński National Park, Poland. 7416 records from The atlas of breeding birds in Małopolska. 13 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 14 records from INRA-Versailles Arabidopsis natural variants. 810 records from Chrysomelidae of the Carpathians. 9 records from Field Museum of Natural History (Zoology) Mammal Collection. 1 records from Lund Museum of Zoology (MZLU). 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 60 records from Shrews of Poland. 1 records from Tallinn Botanic Garden. 26 records from Museum of Comparative Zoology, Harvard University. 822 records from Australia's Virtual Herbarium. 3 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 58 records from Ichthyology Collection - Royal Ontario Museum. 3 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 29444 records from EOD - eBird Observation Dataset. 73 records from iNaturalist Research-grade Observations. 1 records from UCBG TAPIR Provider. 5 records from CONN. 34 records from National System of Protected Areas in Poland - Fungi. 13 records from Aranzadi Ringing Scheme (bird ring-recovery data). 3214 records from Upper Silesian Museum, Bird Observations. 2 records from NYSM Birds. 18 records from Recent Invertebrates Specimens. 16 records from Invertebrates Collection of the Swedish Museum of Natural History. 1894 records from Fungi Collection. 181 records from Alien Species in Poland - Animals. 2 records from Collection botanique Le Grand A. (BOUM). 14 records from Mammals housed at MHNG, Geneva. 2 records from mel. 89 records from Estonian University of Life Sciences. 85 records from Essig Museum of Entomology. 58 records from NMNH occurrence DwC-A. 653 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 18347 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 320 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 3 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 69 records from Unter hellen Zinnen und finsteren Grotten. 14 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 2233 records from Chrysomelidae of Poland. 69 records from Diveboard - Scuba diving citizen science observations. 23 records from Bryophyte herbarium, Trondheim (TRH). 8 records from Illinois Natural History Survey Insect Collection. 3000 records from Polish seed gene bank – historical passport data of accessions. 5045 records from naturgucker. 28 records from Erik Acharius lichen collection. 42 records from UMMZ Mammal Collection. 2 records from Rye, Barley, Oats Genetic Resources. N.I.Vavilov Research Institute of Plant Industry, St. Petersburg. 191547 records from The Distribution Atlas of Butterflies in Poland. 16 records from Western Palaearctic Ectoedemia (Zimmermannia) Hering and Ectoedemia Busck s. str. (Lepidoptera: Nepticulidae): five new species and new data on distribution, hostplants and recognition. 804 records from MfN - Fossil invertebrates Ia. 2 records from MfN - Fossil vertebrates III. 20 records from MfN - Trace fossils. 356 records from MfN - Fossil invertebrates IIb. 1 records from MfN - Fossil invertebrates III. 898 records from MfN - Fossil vertebrates IV. 257 records from MfN - Fossil plants (Cenophytic). 244 records from MfN - Fossil plants (Mesophytic). 1152 records from MfN - Fossil plants (Paleophytic). 2 records from MfN - Fossil vertebrates V. 4 records from ZFMK DORSA. 111035 records from Mammal Collection. 1674 records from KTU Pinophyta. 2 records from Coleoptera. 166 records from Heteroptera. 1 records from MSB Parasite Collection (Arctos). 59 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 25 records from Lichen herbarium, Oslo (O). 935 records from Bats of Poland. 1233 records from Saproxylic Beetles of the Tatra Mts.. 1 records from AlgaTerra. 7 records from LACM Vertebrate Collection. 942 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 7 records from Jardin botanique de Montréal (JBM). 41 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 3 records from IZIKO South Africa Museum Hymenoptera Collection (1800-2013). 48 records from Collection Crustacea - ZMB. 126 records from Collection Vermes - ZMB. 1 records from Collection Polychaeta - ZSRO. 75 records from Tiroler Landesmuseum Ferdinandeum. 21 records from The Fungal Collection at the Botanische Staatssammlung München. 10 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 27 records from The Lichen Collection at the Botanische Staatssammlung München. 2 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 25 records from Tropicos Specimen Data. 141 records from Fig. 7. Relative abundance of ostracod species in composite core JH05. 1500 records from Coleoptera Collection. 7 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 14 records from Western Australian Museum provider for OZCAM. 5 records from AIS Wildtype Populations of Arabidopsis. 516 records from SysTax - Zoological Collections. 7 records from Naturhistorisches Museum Mainz, Botanical Collection. 4 records from Naturhistorisches Museum Mainz, Zoological Collection. 89 records from Amphibian specimens. 196 records from Natural History Museum (London) Collection Specimens. 10539 records from Bumblebees, cuckoobees and butterflies in southern Poland. 11 records from Botanical Museum, Copenhagen, the Phycology Herbarium. 412 records from Natural History Museum, Vienna - Herbarium W. 65 records from Macaulay Library Audio and Video Collection. 307 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 1 records from Harold W. Manter Laboratory of Parasitology Collection. 157 records from IG TUT paleontology. 138 records from Tartu University, palaeontology collections. 27 records from RBINS collections. 12 records from Ohio State University Fish Division (OSUM). 1202 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 612626 records from Ringing Data from the Bird Migration Research Station, University of Gdańsk. 2 records from Field Museum of Natural History (Botany) Fungi Collection. 79 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 30 records from The Fungal Collection of Helga Große-Brauckmann at the Botanische Staatssammlung München. 798 records from Herbarium Senckenbergianum (FR) - Fungi. 2 records from Collection Malakologie - SNSD. 2 records from Collection Ichthyologie - SNSD. 55 records from Collection Soil Aninmals. 14 records from Corvids Literature Database. 4926 records from Edaphobase. 1 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 1 records from Swiss Psyllid (Hemiptera) Collections - Basel. 848 records from Chrysomelidae of Central Europe. 11 records from Parasitic Platyhelminthes Collections. 108 records from Australian National Herbarium (CANB). 11 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 104 records from Australian Antarctic Division Herbarium. 5 records from UWBM Ornithology Collection. 1 records from Real Jardin Botanico, Madrid: MA-Musci. 262 records from Natural Geography In Shore Areas (NaGISA) Dataset. 1 records from Academy of Natural Sciences OBIS Mollusc Database. 433 records from Database on Forest Disturbances in Europe. 1 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 358 records from Invertebrate Collection of Dept. of Ecology. 539 records from Bay of Puck dataset (EurOBIS). 12 records from MarBEF Publication Series data (EurOBIS). 5 records from Botanic Garden of the Finnish Museum of Natural History. 4366 records from Historical quantitative benthos grab samples from the Southern Baltic Sea (EurOBIS). 314 records from Histroical benthic dredge samples from the southern baltic and the North Sea (EurOBIS). 11 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 6 records from Michigan State University Herbarium Lichens. 8309 records from Paleobiology Database. 1 records from NBM birds. 22 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 6 records from Arizona State University Lichen Collection. 18 records from Western Palearctic migratory birds in continental Africa. 81 records from Bryotropha (Lepidoptera: Gelechiidae) in Western Palaearctic. 3 records from University of Alberta Ichthyology Collection (UAMZ). 7 records from NSW herbarium collection. 116 records from Invertebrate Paleontology Division, Yale Peabody Museum. 2 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 1 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 72 records from Herbarium Berolinense. 220 records from Lichen Herbarium Berlin. 358 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 54 records from Biologiezentrum Linz. 240 records from United States National Plant Germplasm System Collection. 31 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 265 records from The Erysiphales Collection at the Botanische Staatssammlung München. 162 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Collection of Hermann Neubert. 26 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Collection of Martin Schnittler. 24 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Main Collection. 4469 records from Coleoptera of Białowieża Forest. 83 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 15 records from The Collection of Fungi of the Real Jardín Botánico of Madrid (MA-Fungi). 8 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 5 records from The Myxomycetes Collection at the V. L. Komarov Botanical Institute, St. Petersburg. 1 records from inatura - Erlebnis Naturschau Dornbirn. 5628 records from EURISCO, The European Genetic Resources Search Catalogue. 15 records from European Moth Nights. 5 records from MAL. 208 records from Naturalis Biodiversity Center (NL) - Aves. 3 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 20 records from Harpactus Shuckard. 2 records from Christopher Walker collection of Glomeromycotan fungi. 75 records from Field Museum of Natural History (Botany) Bryophyte Collection. 478 records from Occurrence of mammalia relicts at site Raj Cave. 1 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 129 records from Occurrence of mammalia relicts at site Koziarna Cave. 1 records from Occurrence of mammalia relicts at site Warsaw. 136 records from Occurrence of mammalia relicts at site Nietoperzowa. 23 records from Occurrence of mammalia relicts at site Oblazowa 2. 62 records from Occurrence of mammalia relicts at site Zawalona Cave. 32 records from Occurrence of mammalia relicts at site Jaskinia Niedwiedzia. 602 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 6226 records from Lichens of North-Eastern Poland. 6 records from Natural History Museum, University of Tartu. 4079 records from Lichens of Biebrza National Park. 13 records from Herbarium of Umeå University (UME). 1741 records from Amphibian observations from Nida Valley. 1 records from Field Museum of Natural History (Botany) Seed Plant Collection. 10 records from Homoptera. 14611 records from Polish gene bank – passport data of plants accessions which are important in human life. 13 records from UA Herbarium. 3 records from R. L. McGregor Herbarium Lichen Collection. 4 records from Therevid PEET Project. 62 records from Texas A&M University Insect Collection. 662 records from Biological and palaeontological collection and observation data MNHNL. 83 records from Entomology Division, Yale Peabody Museum. 53 records from Collection Pisces SMF. 2 records from Collection Arachnology SMF. 1 records from Collection Mollusca SMF. 168 records from Collection Aves (spirit preserved) SMF. 3 records from Collection Herpetology SMF. 13 records from Herbarium Senckenbergianum (FR). 16 records from Collection Aves (bird skeletons) SMF. 207 records from Collection Aves (bird skins) SMF. 39 records from Collection Crustacea SMF. 4 records from SINGER Coordinator. 31 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 11 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 235 records from Herbarium of the Department of Natural Forests (Forest Research Institute) - Lichens. 1 records from SMNS Herpetologie. 1 records from MVZ Egg and Nest Collection (Arctos). 40019 records from Carpatica Operation. 5 records from Bird Specimens. 763 records from Bisons Collection. 1566 records from The DNA and Sample Repository at AIT. 2549 records from KTU Pteridophyta. 142 records from Arachnologie - SMNG. 1236 records from Coleoptera of Biebrza National Park. 1 records from Queensland Museum provider for OZCAM. 9847 records from National System of Protected Areas in Poland - Plants. 375 records from Lund Botanical Museum (LD). 283 records from Snow Entomological Museum Collection. 5 records from Avena wild species VIR Herbarium. N.I.Vavilov Institute of Plant Genetic Resources (VIR). 6 records from Spider Mites Collection of Jean Gutierrez. 1227 records from Geographically tagged INSDC sequences. 21 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 1 records from MSB Host Collection (Arctos). 4 records from William Nylander lichen collection. 316 records from SAFRING: Historical Bird Ringing Records (2005-2009). 7 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 53 records from Animal Sound Archive. 2 records from Bernice P. Bishop Museum. 346 records from Weevils of the Carpathians. 7 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 6056 records from Lichens of Knyszyn Forest. 23 records from Carnet en Ligne. 7 records from Australian National Insect Collection. 53 records from Royal Botanic Garden Edinburgh Herbarium (E). 1459 records from Coleoptera of Kozienice Forest. 2 records from Botany (UPS). 969 records from Coleoptera of Tuchola Forest and Tuchola Forest National Park. 8 records from Instituto de Ciencias Naturales. 299 records from Bat Banding. 22 records from Mammalogy Collection - Royal Ontario Museum. 20513 records from EBCC Atlas of European Breeding Birds. 5 records from My naturesounds - nature observations with sound recordings. 4814 records from Carabidae of the Carpathians. 14 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1120 records from Birds of Cisna Community (southern Poland). 4354 records from Herbarium WRSL, Lichens Collection. 20 records from Entomological specimens of Museum fuer Naturkunde und Vorgeschichte Dessau. 1 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 261 records from Hymenoptera. 6683 records from National System of Protected Areas in Poland - Animals. 130 records from Natural History Museum Rotterdam (NL) - Insecta collection. 322 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 1 records from Nijmegen Natural History Museum (NL) - Entomological Collection. 6 records from Instituto de ciencias naturales. 38 records from Australian Museum provider for OZCAM. 1346 records from Weevils of Poland. 1042 records from Herbarium of University of Białystok - Vascular Plants. 1 records from Entomology at ZMUC, Natural History Musem of Denmark. 244 records from BioFresh Pond Data. 1 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 3 records from MVZ Bird Collection (Arctos). 1 records from Vascular Plant Herbarium, Oslo (O). 2 records from Anymals+plants - Citizen Science Data. 4 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 68 records from Alien Species in Poland - Plants. 1 records from Diptera. 34 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 1 records from Collection Mammalogie - ZSRO. 443 records from Carabidae of Poland. 62 records from Geneva Herbarium – General Collection (G). 2 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 34 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 48913 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 42983 records from Flora of the Stołowe Mts.. 17 records from Lichen herbarium, UiB. 3537 records from Atlas of the Amphibians and Reptiles of Poland.
Keywords: GBIF; biodiversity; species occurrences